Understanding the lifestyle of health and sustainability – an exploratory study. (1st January 2014) - Posegga, Oliver; Zylka, Matthäus Paul; Putzke, Johannes; Fischbach, Kai; Schoder, Detlef
The goal of this paper is to study the psychographic and demographic attributes and the interests of lifestyle of health and sustainability (LOHAS) consumers. Based on a dataset of 3, 813 user profiles from the largest LOHAS community site on Facebook, we applied association rule mining and logistic regression to achieve this goal. We focused our work on applying the collaborative innovation network (COIN) concept to the LOHAS consumer. Results show that LOHAS consumers have a strong spiritual attitude and a general interest in outdoor and fitness activities such as hiking, gardening, and yoga. Finally, we provide a description of a LOHAS consumer profile archetype and compare our findings to existing work.